Child Care Monitoring for a Better Child Health Service - Rajaidup Meliala; S. M. Manoeroeng; Chairuddin P. Lubis; Djaman Purba; Jaminsen Sinaga; Helena Siregar (Indonesian Pediatric Society, 1983)
Three hundred under five years of age patients admitted to Dr. Pirngadi General Hospital Child Health during a two months period (October-November, 1981) were studied, using child care monitoring form. The age group with highest morbidity (86.7%) was found in the age group of 0-2 years. Only 54.3% of the children get breastfeeding until the age of 6 months. Supplementary food was already given at the age of 0-4 months. Undernutrition was still high (41.7%) particularly under the age of 2 years (32.7%). BCG and DPT immunization were still low respectively 22.7% and 10%. Gastrointestinal disease and respiratory tract infection were the two leading diseases; tetanus neonatorum was also frequent. The percentage of discharge on parents request was high (31%) which might be related to low level parental education and low socio economic condition.